2004
DOI: 10.1111/j.0141-6707.2004.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Helminth risks associated with mixed game and livestock interactions in and around Lake Mburo National Park, Uganda

Abstract: A study was performed in and around Lake Mburo National Park (LMNP) to identifycommon helminths that parasitize both game and livestock. Various techniques including £oatation, Baerman and sedimentation tests, faecal culturing and post-mortem were used to identify helminths recovered during the survey. Identi¢cation was based on egg, larval and adult helminth developmental stages. Results showed that 22 species of parasitic nematodes, lungworms, ascaris, trematodes and tapeworms occur in both wild game and liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 2 publications
(1 reference statement)
1
21
0
Order By: Relevance
“…A recent investigation (Ocaido et al, 2004) has shown that F. gigantica is one of the most widespread helminths among wildlife in and around Lake Mburo National Park in Uganda, confirming earlier reports by Hammond and Sewell (1993) and Okao (1975), that in Uganda F. gigantica can be maintained in wildlife without the presence of domestic livestock. The reports on Fasciola in both wildlife and livestock, combined with the large geographical areas of suitable L. natalensis habitat modeled for Uganda, indicate a potential human and livestock health risk, especially in areas around national parks were mixed game and livestock production systems exists (Ocaido et al, 2004). To evaluate the magnitude of human risk to fascioliasis in Uganda, epidemiological studies in areas overlapping with modeled suitable habitats for L. natalensis should be undertaken.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A recent investigation (Ocaido et al, 2004) has shown that F. gigantica is one of the most widespread helminths among wildlife in and around Lake Mburo National Park in Uganda, confirming earlier reports by Hammond and Sewell (1993) and Okao (1975), that in Uganda F. gigantica can be maintained in wildlife without the presence of domestic livestock. The reports on Fasciola in both wildlife and livestock, combined with the large geographical areas of suitable L. natalensis habitat modeled for Uganda, indicate a potential human and livestock health risk, especially in areas around national parks were mixed game and livestock production systems exists (Ocaido et al, 2004). To evaluate the magnitude of human risk to fascioliasis in Uganda, epidemiological studies in areas overlapping with modeled suitable habitats for L. natalensis should be undertaken.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, there has been speculation about the part possibly played by wild African ruminants in the epidemiology of fascioliasis, both in relation to infection of domestic livestock and out of concern for the potential damage that fascioliasis could cause to wildlife confined within reserves (Hammond, 1972;Brown, 1994). A recent investigation (Ocaido et al, 2004) has shown that F. gigantica is one of the most widespread helminths among wildlife in and around Lake Mburo National Park in Uganda, confirming earlier reports by Hammond and Sewell (1993) and Okao (1975), that in Uganda F. gigantica can be maintained in wildlife without the presence of domestic livestock. The reports on Fasciola in both wildlife and livestock, combined with the large geographical areas of suitable L. natalensis habitat modeled for Uganda, indicate a potential human and livestock health risk, especially in areas around national parks were mixed game and livestock production systems exists (Ocaido et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Njoroge et al (2002) reported a prevalence of 19.4%, 3.6%, 4.5% and 61.4% in cattle, sheep, goats and camels respectively in Kenya. The disease was also reported in domestic and wildlife in Uganda (Ocaido et al 2004). Ngowi et al (2004) reported a prevalence of 4.3% in pigs in northern Tanzania.…”
Section: Introductionmentioning
confidence: 78%
“…Previous work (Ocaido 1995;Ocaido et al 2006;Mugisha et al 2005) on disease problems in the study area suggested that Ticks and Tick Borne Diseases (TTBDs) were the major constraint to cattle production. R. appendiculatus, the vector of East Coast Fever (ECF), was found to be the most abundant tick species (Ocaido et al 2006).…”
Section: Introductionmentioning
confidence: 90%